2021
DOI: 10.3390/cancers13184721
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular HSP70 in the Function of Tumor-Associated Immune Cells

Abstract: Extracellular vesicles released by tumor cells (T-EVs) are known to contain danger-associated molecular patterns (DAMPs), which are released in response to cellular stress to alert the immune system to the dangerous cell. Part of this defense mechanism is the heat shock protein 70 (HSP70), and HSP70-positive T-EVs are known to trigger anti-tumor immune responses. Moreover, extracellular HSP70 acts as an immunogen that contributes to the cross-presentation of major histocompatibility complex (MHC) class I molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 149 publications
0
20
0
Order By: Relevance
“…Extracellular Hsp70 is enhancing tumor growth and migration by promoting multiple pro-oncogenic pathways including the PI3K/Akt and phosphorylated STAT3 pathways (Lee et al 2006 ; Diao et al 2015 ; Park et al 2017 ). Moreover, extracellular Hsp70 levels have been found to affect tumor associated immune responses (Linder and Pogge von Strandmann 2021 ; Pockley and Henderson 2018 ) and exosomal Hsp70 acts as a regulator of tumor-associated immune cells which determines immunosurveillance and evasion (Multhoff et al 2001 ; Lee et al 2006 ; Specht et al 2015 ; Barreca et al 2017 ; Taha et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Hsp70 is enhancing tumor growth and migration by promoting multiple pro-oncogenic pathways including the PI3K/Akt and phosphorylated STAT3 pathways (Lee et al 2006 ; Diao et al 2015 ; Park et al 2017 ). Moreover, extracellular Hsp70 levels have been found to affect tumor associated immune responses (Linder and Pogge von Strandmann 2021 ; Pockley and Henderson 2018 ) and exosomal Hsp70 acts as a regulator of tumor-associated immune cells which determines immunosurveillance and evasion (Multhoff et al 2001 ; Lee et al 2006 ; Specht et al 2015 ; Barreca et al 2017 ; Taha et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] For example, heat shock proteins (HSPs) can chaperone TAAs, protect them and facilitate their uptake by APCs with subsequently endorsed cross‐presentation. [ 17 ] Inspired by natural chaperones, various chaperone mimetic materials have been designed and used to regulate protein (re)folding, protect protein, and mediate protein transport. [ 18 ] Recently, in a proof‐of‐concept study, we first time demonstrated that the mixed‐shell polymeric micelle (MSPM)‐based nanochaperone (nChap) was a promising nanomaterial for fabrication of nanovaccine to enhance cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, exosomes have been thought to only function as molecular carriers that carry waste from cells; however, it has become clear that EVs affect various biological processes and diseases, including immune responses and cancer [ 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 ]. Nonetheless, it is difficult to identify these exosomes.…”
Section: Ev-mediated Immune Escape Of Cancer Cellsmentioning
confidence: 99%